Blood advanced glycation end products and biomarkers of inflammation in class III obese Brazilian subjects. Issue 2 (27th March 2017) - Silva, Thiago Lenoir da; Linhares, Rose Marie Muller; Remor, Aline Pertile; Ghisoni, Karina; Martins, Roberta de Paula; Poli, Anicleto; Jr, Aderbal Aguiar; Ronsoni, Marcelo Fernando; Hohl, Alexandre; Walz, Roger; Latini, Alexandra
No abstract available